PENGARUH LAMA PERENDAMAN PANAS DALAM PENGAWETAN LIMA JENIS KAYU DENGAN METODE RENDAMAN PANAS DINGIN - Pipin Permadi; Barly Barly (Jurnal Penelitian Hasil Hutan, 1989)
Wood preservative penetration and retention on five wood species using hot and cold bath process was studied. Wood samples measuring 5 cm x 5 cm x 60 cm were immersed in BFCA preservative solution under temperature of 70° C for nil (control), one, two and three hours then cooled for a day.The result indicates that red meranti (Shorea platycados V.Sl .) is more permeable compared with other species (bangkirai, bungur, damar laut and kapur). In red meranti, one hour immersion in hot preservative yields penetration which conforms with the SKI C-bo-008 Standard for wood building, whereas in other 4 species, the treatment does not seem to be more superior. compared with cold immersion method.